Improving the Standard of Living and Health Status of the RW 07 Community Through Health Education - Yuliani, Yuliani; Melia, Stephani; Riana, Asysyifa; Ginting, Monika; Prasetyaningrum, Widyadari; Tanti, Lanny (CV Media Inti Teknologi, 2024)
Efforts are made in realizing the highest degree of public health as one of the investments for the development of productive human resources. Given some health problems that occur in society today such as hypertension and rheumatism. The purpose of this community service is to increase public knowledge about hypertension, rheumatism, and healthy living. The method used in this service is by using counseling, pre-test and post-test methods. There are several stages used in this activity, namely the pre-test stage, medical examination, counseling, and continued with the post test. The results obtained from this activity, namely from the results of the pre-test and post-test that have been carried out, it can be seen that the influence of education on knowledge and attitudes about hypertension and rheumatism as well as a balanced nutritional diet is very significant in order to improve the degree of health of the community in RW 07 tile village. The conclusion of this activity is that this community service activity has a very good impact on the community.